2009
DOI: 10.1007/s00542-008-0760-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analyses of peel demolding for UV embossing of high aspect ratio micro-patterning

Abstract: Ultraviolet (UV) embossing, involving molding against micro-structured molds, is a quick and efficient method to mass produce high aspect ratio micro-features. A crucial challenge to the repeatability and large-scale application of this technique is successful demolding, which escalates in difficulty with increasing aspect ratio, due to increased polymer-mold mechanical interlocking. Some of the key factors affecting UV embossing include the crosslinked polymer shrinkage and material properties, interfacial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…In the first step following the works of Chan-Park, Yeo, and Shibata, thermal contraction was used to simulate polymerization shrinkage caused by UV curing of the resist. A pseudothermal expansion coefficient was assigned only to the resist and the equivalent shrinkage strain (measured from the experiment) was applied by cooling down the assembly to an appropriate temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step following the works of Chan-Park, Yeo, and Shibata, thermal contraction was used to simulate polymerization shrinkage caused by UV curing of the resist. A pseudothermal expansion coefficient was assigned only to the resist and the equivalent shrinkage strain (measured from the experiment) was applied by cooling down the assembly to an appropriate temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Friction can be ignored, however, if lateral shrinkage of the resist breaks the resist free of the stamp sidewalls eliminating contact during demolding. 53,54 In our study in order to obtain more accurate results, friction was not ignored. To obtain friction coefficients at the resist/stamp interface, friction force microscopy was conducted using a commercial atomic force microscopy (AFM, Agilent 5500).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amirsadeghi [27] [33] 研究了交联收缩、 固化材料模量、交界破坏强度和韧性以及脱模的加载 方式对脱模应力的影响, 获得了实现最小主应力的最 优收缩量. Yeo等人 [34] 运用超弹性材料模型建立了率 无关内聚力模型, 研究了深宽比为14的微细结构的脱 膜工艺, 优化了脱模过程并获得了最优收缩量.…”
Section: 残余层是充型过程中的另一类缺陷 对光线吸unclassified
“…Their results showed that interfacial delamination of the organic and inorganic layers is predominant when short cracks form between the layers; at considerable crack lengths, failure results mainly from channel cracking in the inorganic layer. Yeo et al (2009) employed numerical simulations for determining the microstructural stresses exerted during peel demolding in the ultraviolet embossing process. Cohesive zone modeling was used to model the interface between the resin and the mold.…”
Section: Introductionmentioning
confidence: 99%